Parasitic Infections (Helminth and Protozoa) in Cases Referring to Yazd Central Laboratory, 2002-2004 - AA Dehghani; A Rajabion; MH Anvary; M Ebadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2008)
Introduction: Intestinal parasites have world wide prevalence and are considered to be as one of the leading hygienic and economic problems in the world. It can be said that there is nowhere in the world without parasitic infestations. The present study was conducted to determine the prevalence of intestinal parasites in patients referring to Yazd Central Laboratory in 2000-2002. Methods: The present study was a cross-sectional, analytic and descriptive study including 13388 stool specimens examined by two methods; Formalin-Ethyl Acetate and direct Method for intestinal parasites and Scotch tape method for Enterobius vermicularis. Results: 13388 samples examined included 6913 women and 6475 men. Parasites were observed in 1151 cases (8.6%) including 618 (53.7%) men and 533 (46.3%) women, respectively. Of these, 98.6% were infected with protozoa and 1.4% with helminths. Giardia lambdia (41.05%), E.coli (27.45%) and Blastocystis hominis (15.51%) were the most common infecting organisms. Helminth infections were few, but the highest frequency was related to Hymenolepis nana and Enterobious vermicularis. Maximum frequency was reported in summer. There was a significant association between stool consistency and infestation by intestinal parasites (P=0.002). There was a significant relationship with sex, too (P=0.001) Conclusion: In the present study, the most common parasites were Giardia, E.coli and Blastocystis hominis (higher than five), but the prevalence was less as compared to previous similar studies in other regions, which could be because of the hot and dry weather, better personal hygiene and improved sewage system of Yazd.